Escape from self: Stress increase consumers' preference for experiences over material possessions - Zhao, Yurou; Jin, Xiaotong; Zhao, Taiyang; Li, Jianan (Frontiers in Public Health, 2023)
Considering the theory of self-escape, this research systematically investigates the effect of stress on consumers’ preference for experiences versus material possessions. The findings of the three studies revealed that stress increases consumers’ preference for experiences over material possessions. Additionally, self-escape motivation plays a mediating role between stress and preference for experiential consumption (vs. material consumption). Stress as a self-threat triggers individuals’ motivation to escape from negative self-concept, and experiences can help individuals temporarily escape from negative self-recognition and provide more leisure value than material possessions. Therefore, individuals increase their consumption preference for experiences. Furthermore, we observed that the type of experiences plays a moderating role between stress and preference for experiential consumption (vs. material consumption). Specifically, compared with low cognitive resource–demanding experiences, the effect of stress on experiential consumption disappears when experiences have a high demand for cognitive resources. These findings extend the research on stress, experiential consumption and material consumption and provides significant advice for public mental health.